2007
DOI: 10.1111/j.1439-0418.2007.01219.x
|View full text |Cite
|
Sign up to set email alerts
|

Lepidopteran cereal stemborers and associated natural enemies on maize and wild grass hosts in Cameroon

Abstract: In Cameroon, the noctuid Busseola fusca is the most important pest of maize. The braconid Cotesia sesamiae, which is the most common larval parasitoid of noctuid stemborers in eastern Africa, was absent on B. fusca attacking maize. Thus, it is planned to introduce several strains of the parasitoid from Kenya. Pre-release surveys were undertaken in major maize growing areas to catalogue stemborer species, and larval and pupal parasitoids on maize and four wild host plant species. On maize, B. fusca was the pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 30 publications
(69 reference statements)
7
78
1
Order By: Relevance
“…A C. sesamiae biotype from inland Kenya successfully developed on B. fusca while the coastal strain was completely encapsulated by B. fusca (Ngi-Song et al, 1998;Zhou et al, 2003). A number of surveys have shown that C. sesamiae is rare in western Africa (Bosque-Pérez et al, 1995;Conlong, 2001;Ndemah et al, 2001Ndemah et al, , 2007, whereas in East and southern Africa, it is a common parasitoid of S. calamistis and B. fusca (Ingram, 1958;Kfir and Bell, 1993;Kfir, 1995Kfir, , 1998.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A C. sesamiae biotype from inland Kenya successfully developed on B. fusca while the coastal strain was completely encapsulated by B. fusca (Ngi-Song et al, 1998;Zhou et al, 2003). A number of surveys have shown that C. sesamiae is rare in western Africa (Bosque-Pérez et al, 1995;Conlong, 2001;Ndemah et al, 2001Ndemah et al, , 2007, whereas in East and southern Africa, it is a common parasitoid of S. calamistis and B. fusca (Ingram, 1958;Kfir and Bell, 1993;Kfir, 1995Kfir, , 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Economic damage to cultivated gramineous crops in West Africa is restricted to the forest and forestsavanna transition zones, and the mid-altitude region (Schulthess et al, 1997). Extensive surveys conducted in several western African countries showed that larval parasitization of stemborers was generally low and considered insufficient for stemborer suppression in agricultural crops (Gounou et al, 1994;Bosque-Pérez et al, 1995;Conlong, 2001;Ndemah et al, 2001Ndemah et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, very little was known about Acrapex host preferences as specimens had been obtained mainly from light trap collections. Extensive surveys conducted since 2004 (Le Ru et al 2006Ru et al a, 2006bOng'amo et al 2006Ong'amo et al , 2013Ong'amo et al , 2014Ndemah et al 2007;Matama-Kauma et al 2008;Moolman et al 2014) in several sub-Saharan countries, targeting wild habitats rich in Poaceae and combining infested host plant collections and light traps, allowed us to obtain several hundred specimens of Acrapex. A recent study by Le Ru et al (2014) focused on a LE RU B. et al, Contribution to Acrapex systematics 3 small group of morphologically related species belonging to subsets of two (groups B and C) of the four morphological groups that have been defined by Berio (1973) based on male genitalia.…”
Section: Introductionmentioning
confidence: 99%
“…Different biotypes of Cotesis sesamian had been successfully introduced into Cameroon for controlling Busseola fusca (Ndemah et al, 2007). So, when choosing natural enemies for biological control program, the different biotypes even from the same species of parasitoid wasp need to be considered carefully.…”
Section: Massicus Raddei Is With Higher Parasitism Rate In Parasitizingmentioning
confidence: 99%